Confinement of fermions by mixed vector-scalar linear potentials in two-dimensional space-time - de Castro, A. S. (Elsevier B.V., 2002)
The problem of confinement of fermions in 1 + 1 dimensions is approached with a linear potential in the Dirac equation by considering a mixing of Lorentz vector and scalar couplings. Analytical bound-states solutions are obtained when the scalar coupling is of sufficient intensity compared to the vector coupling. (C) 2002 Elsevier B.V. B.V. All rights reserved.